National Inmate Survey (NIS) - Jails: Full Survey Respondents, (United States), 2007 ([Verlag nicht ermittelbar], 2018)
The National Inmate Survey (NIS) is part of the Bureau of Justice Statistics' (BJS) National Prison Rape Statistics Program, which gathers mandated data on the incidence and prevalence of sexual assault in correctional facilities under the Prison Rape Elimination Act of 2003 (PREA; P.L. 108- 79). Inmates are randomly assigned to receive either a survey of sexual victimization or a survey of mental and physical health, past drug and alcohol use, and treatment for substance abuse. About 88 percent of the respondents completed modules through the survey of sexual victimization while the other 12 percent completed modules through the alternative survey. However, the data in this study focuses solely upon substance use and treatment. No respondent answered questions about sexual victimization. The same 37,0888 respondents who are in this data are also part of the 79,973 respondents from the study National Inmate Survey (NIS) - Jails: Full Survey Respondents, [United States], 2007-2009 (ICPSR 37011).